Предмет: Алгебра,
автор: baty6767
z1+z2=3i+(2-3i)
z1+z2=(6+2i)-(7+2i)
Z1•z2=(3-2i)•(4+3i)
Ответы
Автор ответа:
0
z₁+z₂=2+(3-3)i=2+0i=2
z₁+z₂=(6-7)+(2-2)i=-1+0i=-1
z₁z₂=12+9i-8i-6i²=12+i+6=18+i
i²=-1
z₁+z₂=(6-7)+(2-2)i=-1+0i=-1
z₁z₂=12+9i-8i-6i²=12+i+6=18+i
i²=-1
Автор ответа:
0
4 с минусом поставили
Похожие вопросы
Предмет: Обществознание,
автор: sofiy082007
Предмет: Алгебра,
автор: grovepad89
Предмет: Информатика,
автор: hs4
Предмет: Математика,
автор: аывав
Предмет: Биология,
автор: alek0021000